Secondary mineralization processes in the assessment of alkaline reactivity of aggregates and durability of concrete - Agnieszka Pękala; Sylvia Vilcekova (Case Studies in Construction Materials)
According to the latest RILEM guidelines and regulations, mineral aggregates, which are the main component of concrete, are often responsible for the destruction of building structures resulting from the alkali-aggregate reaction (AAR). This process is influenced by both the mineral composition of individual rock components present in the aggregate, as well as their structural and textural features. The presented work presents the results of petrographic analyses performed to identify rocks and potentially reactive components that cause the ASR (alkali silica reaction), reaction in concrete. As part of the mineral evaluation, reactive siliceous phases were identified. An analysis was also carried out regarding the internal structure of the minerals, identifying single-crystalline quartz and polycrystalline quartz with a mosaic structure or in a state of internal stress. Attention was paid to secondary mineralisation processes affecting the reactivity of concrete. The following processes were identified: silicification, sericitisation, pyritization in aggregates. The conducted mineralogical and petrographic tests confirmed that the cause of the destructive expansion of the tested concrete is the alkali-silica reaction, caused by the identified reactive components and secondary mineralisation processes.